Pengaruh Harga, Promosi, Lokasi, Kelengkapan Produk Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen (Studi Kasus pada Mahasiswa UNISMA yang Berbelanja di Indomaret) - Musmuliadin Musmuliadin; Agus Widarko; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract This study aims to determine and analyze the effect of price, promotion, location, product completeness and service quality on consumer satisfaction of UNISMA students who shop in Indomaret either partially or simultaneously. The population and sample in this study were 85 people. Data collection through questionnaires. Data analysis in this study used SPSS version 14 with data testing techniques used in this study include multiple linear regression test, and testing of research hypotheses. The results of the analysis show that location does not significantly influence customer satisfaction, price, promotion, product humidity and service quality significantly influence customer satisfaction. Simultaneously shows that price, promotion, location, product completeness and service quality influence consumer satisfaction of UNISMA students who shop at Indomaret.Keywords: Price, Promotion, Location, Product Completeness and Service Quality Towards Consumer Satisfaction.